Involvement of the Sieve Element Cytoskeleton in Electrical Responses to Cold Shocks(1)([W]) - Hafke, Jens B. (American Society of Plant Biologists, 2013)
This study dealt with the visualization of the sieve element (SE) cytoskeleton and its involvement in electrical responses to local cold shocks, exemplifying the role of the cytoskeleton in Ca(2+)-triggered signal cascades in SEs. High-affinity fluorescent phalloidin as well as immunocytochemistry using anti-actin antibodies demonstrated a fully developed parietal actin meshwork in SEs. The involvement of the cytoskeleton in electrical responses and forisome conformation changes as indicators of Ca(2+) influx was investigated by the application of cold shocks in the presence of diverse actin disruptors (latrunculin A and cytochalasin D). Under control conditions, cold shocks elicited a graded initial voltage transient, ΔV(1), reduced by external La(3+) in keeping with the involvement of Ca(2+) channels, and a second voltage transient, ΔV(2). Cytochalasin D had no effect on ΔV(1), while ΔV(1) was significantly reduced with 500 nm latrunculin A. Forisome dispersion was triggered by cold shocks of 4°C or greater, which was indicative of an all-or-none behavior. Forisome dispersion was suppressed by incubation with latrunculin A. In conclusion, the cytoskeleton controls cold shock-induced Ca(2+) influx into SEs, leading to forisome dispersion and sieve plate occlusion in fava bean (Vicia faba).